1997
DOI: 10.1128/mcb.17.5.2566
|View full text |Cite
|
Sign up to set email alerts
|

Novel Gal3 Proteins Showing Altered Gal80p Binding Cause Constitutive Transcription of Gal4p-Activated Genes in Saccharomyces cerevisiae

Abstract: Gal4p-mediated activation of galactose gene expression in Saccharomyces cerevisiae normally requires both galactose and the activity of Gal3p. Recent evidence suggests that in cells exposed to galactose, Gal3p binds to and inhibits Gal80p, an inhibitor of the transcriptional activator Gal4p. Here, we report on the isolation and characterization of novel mutant forms of Gal3p that can induce Gal4p activity independently of galactose. Five mutant GAL3 c alleles were isolated by using a selection demanding consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
103
1
3

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(107 citation statements)
references
References 78 publications
0
103
1
3
Order By: Relevance
“…Gal3p is a paralog of Gal1p (4), the galactokinase and the first enzyme of the galactose utilization pathway, but Gal3p does not have galactokinase activity (5,6). Any one of several mutations dispersed in the Gal3p sequence (GAL3 constitutive mutant) causes the activation of GAL genes in the absence of galactose (7). Biochemical studies have shown that Gal3p directly interacts with Gal80p in a galactose-and ATPdependent manner (3,8), and that the Gal3p constitutive mutants interact with Gal80p in the absence of galactose (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Gal3p is a paralog of Gal1p (4), the galactokinase and the first enzyme of the galactose utilization pathway, but Gal3p does not have galactokinase activity (5,6). Any one of several mutations dispersed in the Gal3p sequence (GAL3 constitutive mutant) causes the activation of GAL genes in the absence of galactose (7). Biochemical studies have shown that Gal3p directly interacts with Gal80p in a galactose-and ATPdependent manner (3,8), and that the Gal3p constitutive mutants interact with Gal80p in the absence of galactose (7).…”
mentioning
confidence: 99%
“…Any one of several mutations dispersed in the Gal3p sequence (GAL3 constitutive mutant) causes the activation of GAL genes in the absence of galactose (7). Biochemical studies have shown that Gal3p directly interacts with Gal80p in a galactose-and ATPdependent manner (3,8), and that the Gal3p constitutive mutants interact with Gal80p in the absence of galactose (7). How the formation of the Gal3p-Gal80p complex transmits the galactose signal to the Gal80p-Gal4p complex in the nucleus to activate Gal4p has been unclear.…”
mentioning
confidence: 99%
“…ScPD2 was derived from ScVP2-103 (Pilauri et al 2005) by disruption of the GAL1 gene. Sc750 and Sc751 were derived from Sc724 (Blank et al 1997) by disruption of the GAL80 gene and integration of the GAL80 S-0 and GAL80 S-1 alleles, respectively. The GAL80 S-2 mutation was not integrated into the genome, but instead was carried on a CEN plasmid (pMPW87).…”
Section: Methodsmentioning
confidence: 99%
“…Gal3 C proteins bind to Gal80 in the absence of galactose and cause constitutive expression of the GAL genes (Blank et al 1997). A suppressor (GAL3 SOC ) of GAL3 C mutations and four suppressible alleles (GAL3 C -F237Y, -V396A, and -S509P/L) colocalize to a region in the Gal3 model that contains a putative ligand-regulated hinge region previously identified in a KlGal1 homology model (Menezes et al 2003).…”
mentioning
confidence: 98%
See 1 more Smart Citation